Influence of Methylprednisolone Pulse Therapy on Liver Function in Patients with Graves’ Orbitopathy - Piotr Miśkiewicz; Anna Jankowska; Kinga Brodzińska; Justyna Milczarek-Banach; Urszula Ambroziak (International Journal of Endocrinology)
Purpose. Intravenous methylprednisolone (IVMP) pulse therapy is the first-line treatment in active moderate-to-severe Graves’ orbitopathy (GO) and dysthyroid optic neuropathy (DON). One of the adverse effects of this therapy is liver dysfunction that can be mild (ALT < 100 U/L), moderate (ALT: 100–300 U/L), and severe defined as acute liver injury (ALI) (ALT > 300 U/L). ALI can be irreversible and fatal. The aim of the study was to evaluate the influence of two different schemes of therapy with IVMP in moderate-to-severe GO and DON on biochemical liver parameters. Materials and Methods. 49 patients with moderate-to-severe GO were treated with IVMP in every week schedule (cumulative dose 4.5 g), and 19 patients with DON received 3.0 g IVMP (1.0 g/day for 3 consecutive days). AST, ALT, and total bilirubin were measured before treatment and after IVMP in the following selected pulses: after 0.5 g (A1), 3.0 g (A2), and 4.5 g (A3) in the group with moderate-to-severe GO and after 3.0 g IVMP in the group with DON (B1). Results. We observed a statistically higher level of AST and ALT after therapy with 3.0 g of IVMP (B1) than after 0.5 g (A1), 3.0 g (A2), and 4.5 g of IVMP (A3). Mild elevation of ALT was found in 4% and 11% of patients with moderate-to-severe GO and DON, respectively. Moderate elevation of ALT was found in 0% and 21% of patients with moderate-to-severe GO and DON, respectively. There were no cases of ALI. Conclusion. Therapy of GO with higher doses (1.0 g) of IVMP in consecutive days is associated with higher risk of liver damage than treatment with moderate doses (≤0.5 g) in every week schedule. This trial is registered with NCT03667157.